역률을 고려한 불연속 변조 기반 전력 반도체의 온도 저감 기법 - 이경구; 최혜원; 이교범 (조명.전기설비학회논문지, 2025)
This paper proposes a thermal reduction method for SiC modules using discontinuous PWM (DPWM) based on power factor. Thermal management is critical to improving the reliability and efficiency of inverter systems ensuring significantly lower costs in various applications. An active thermal controls based on modulation schemes have been presented to alleviate thermal stress on the power modules while maintaining optimal power quality without additional hardware or software. The power loss and thermal stress of SiC module are analyzed according to the modulation schemes such as sinusoidal PWM (SPWM), space vector PWM (SVPWM), and DPWM in this paper. In addition, The thermal reduction of DPWM schemes at clamping regions and power factor are analyzed to reduce the thermal of the SiC module. The proposed thermal reduction method is demonstrated by various simulation results.
Keywords: Active thermal control; Discontinuous PWM; Power factor; SiC module; Thermal reduction